2022
DOI: 10.1111/nph.18485
|View full text |Cite
|
Sign up to set email alerts
|

Increased bundle‐sheath leakiness of CO2 during photosynthetic induction shows a lack of coordination between the C4 and C3 cycles

Abstract: Summary Use of a complete dynamic model of NADP‐malic enzyme C4 photosynthesis indicated that, during transitions from dark or shade to high light, induction of the C4 pathway was more rapid than that of C3, resulting in a predicted transient increase in bundle‐sheath CO2 leakiness (ϕ). Previously, ϕ has been measured at steady state; here we developed a new method, coupling a tunable diode laser absorption spectroscope with a gas‐exchange system to track ϕ in sorghum and maize through the nonsteady‐state co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Alternatively, if the CCM is faster to activate during light induction than the C3 cycle there could be transient over-pumping of CO2 and an increase in BS leakiness -where CO2 diffuses out of BS cells back into M cells, raising the energetic cost of carbon fixation due to the futile cycling of PEP. Greater BS leakiness during induction relative to steady state has been previously observed in maize and sorghum (Wang et al, 2022). Lags in CCM deactivation during transitions to lower light could also increase leakiness and reduce quantum yields if Mal/Asp accumulated in the BS is decarboxylated despite insufficient C3 cycle activity.…”
Section: Introductionmentioning
confidence: 76%
“…Alternatively, if the CCM is faster to activate during light induction than the C3 cycle there could be transient over-pumping of CO2 and an increase in BS leakiness -where CO2 diffuses out of BS cells back into M cells, raising the energetic cost of carbon fixation due to the futile cycling of PEP. Greater BS leakiness during induction relative to steady state has been previously observed in maize and sorghum (Wang et al, 2022). Lags in CCM deactivation during transitions to lower light could also increase leakiness and reduce quantum yields if Mal/Asp accumulated in the BS is decarboxylated despite insufficient C3 cycle activity.…”
Section: Introductionmentioning
confidence: 76%
“…Photosynthetic induction in C 4 plants is slower than in closely related C 3 species and, in NADP-ME dicot Flaveria bidentis, the inefficiency was attributed to an incomplete suppression of photorespiration caused by a slow build-up of the C 4 cycle intermediates (Arce Cubas et al, 2023;Sage and McKown, 2006). Alternatively, Rubisco activation was proposed as a primary cause of lost efficiency based on the increased leakiness of CO 2 detected during the photosynthetic induction in NADP-ME monocots, maize and sorghum, and metabolic modelling of NADP-ME C 4 photosynthesis (Wang et al, 2021(Wang et al, , 2022. In this work, similar levels of PhiPSII between control and transgenic plants in the beginning of induction suggested unaltered linear electron flow rate (Figure 6), whilst the faster establishing of NPQ in plants with increased Rieske content indicated that more pmf was generated, likely, via cyclic electron flow.…”
Section: Discussionmentioning
confidence: 99%
“…The LI-COR 6800 gas exchange system (LI-COR Environmental) was coupled to a tunable-diode laser absorption spectroscope (TDLAS model TGA 200A; Campbell Scientific) to measure online carbon isotope discrimination 65,66 . The TDL was connected to the LI-6800 reference and sample air streams using the ports on the back of the sensor head.…”
Section: Methodsmentioning
confidence: 99%